2008
DOI: 10.1108/17468770810916195
|View full text |Cite
|
Sign up to set email alerts
|

The effects of country‐of‐origin on Chinese consumers' wine purchasing behaviour

Abstract: PurposeThis research is designed to explore Chinese customers' wine purchasing behaviours and to investigate the effect of country‐of‐origin (COO) information on their wine evaluations.Design/methodology/approachData were collected from the shopping malls both in Shanghai and Hangzhou, China, using the systematic sampling method. A total 148 usable questionnaires were returned and analysed by SPSS.FindingsThe results confirmed that Chinese customers consider COO as the most important factor in their wine evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 55 publications
3
68
1
5
Order By: Relevance
“…Generally, Western wine brands are favored by Chinese consumers, especially for important social and cultural occasions such as gift giving (Li and Su 2007;Shi et al 2011). Western brands are more likely to be approved by the gift recipient or relevant third parties, as well as guaranteeing a quality and prestigious status (Hu et al 2008). Furthermore, individuals are more willing to pay higher prices and increase selection efforts in GGW to avoid Blosing face^(being disapproved by the recipient or the public) (Hu et al 2008).…”
Section: The Grape Wine Marketmentioning
confidence: 99%
“…Generally, Western wine brands are favored by Chinese consumers, especially for important social and cultural occasions such as gift giving (Li and Su 2007;Shi et al 2011). Western brands are more likely to be approved by the gift recipient or relevant third parties, as well as guaranteeing a quality and prestigious status (Hu et al 2008). Furthermore, individuals are more willing to pay higher prices and increase selection efforts in GGW to avoid Blosing face^(being disapproved by the recipient or the public) (Hu et al 2008).…”
Section: The Grape Wine Marketmentioning
confidence: 99%
“…However this does not mean that they have a low image of their domestic brands, especially if they have been consuming them for many years and they offer better value for money (Kinra, 2006) or they are seen as being both global and local (Alden, Kelly, Riefler, Lee, & Soutar, 2013). Conversely, consumers from developing countries may buy cheap local brands for private consumption and more expensive foreign brands for public consumption (Hu et al, 2008). Hence, the relationship between COS and home product country image among consumers from developing countries may contain two opposing aspects of images.…”
Section: Cosmopolitanism In Developed and Developing Countriesmentioning
confidence: 98%
“…This lack of conclusive evidence is consistent with other research on the related concept of Country-of-Origin (COO) in developed and developing countries. Some studies show consumers in developing countries have a clear preference for foreign goods (Ettenson, 1993;Wang & Yang, 2008) whereas other studies in developing countries show more complex differences based on such areas as whether the product is purchased for personal or public consumption (Hu, Li, Xie, & Zhou, 2008), perceptions about home country products (Kinra, 2006;Li, Fu, & Murray, 1997) and the degree of global brand localization over time (Jin, Chansarkar, & Kondap, 2006). From the existing evidence, it is not clear in general whether the differences between the PCIs of developed and developing countries are greater than the differences between individual countries.…”
Section: Pci In Developed and Developing Countriesmentioning
confidence: 99%
“…It leads to the consequence, similarly to product, that perceived quality also plays an important part of brand perception (Lee et al, 2008). When consumers perceive the difference among the brands, they will perceive unlike quality too; besides familiarity with a brand name partly impacts on consumers' quality evaluation (Xiaoling, Leeva, Charlene, & Jun, 2008) and this recognition varies through amount of effects by different brands (Kurt, 2005).…”
Section: Brandmentioning
confidence: 99%
“…Brands are the aggregation of all images about a specific company or product that consumers have and brands may take the place of numerous attributes such as quality (Xiaoling et al, 2008;Lockshin, Rasmussen, & Cleary, 2000), thus brands play a significant role to consumers' evaluation and take part in consumers' choice process (Hoyer & Brown, 1990;Dillion, Madden, Kirmani, & Mukherjee, 2001). Many scholars demonstrated that consumers perceive global brands with higher price and better quality (Cattin et al, 1982;Tse & Gorn, 1993;Samiee, 1994;Thakor & Lavack, 2003); as a result, global brands effect positively on consumers' assessment.…”
Section: Brandmentioning
confidence: 99%